Penerapan Finite State Automata Pada Transaksi Via Mobile Banking (Aplikasi BRImo) - Talahaturuson, Januar C.; Pakereng, Magdalena A. Ineke (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The purpose of this study is the application of Finite State Automata on the BRImo mobile banking application. The result of this study is a simulation of the mobile banking application on the BRImo application related to the application of Finite State Automata which is used in the transaction process via the BRImo mobile banking application. The results show that Finite State Automata can be used as the basic logic to process the BRImo application mobile banking transaction which divides each system into state forms.